Pengaruh Model Pembelajaran Two Stay Two Stray terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS - Fitriani, Nurul; Suandi, Suandi; Muzakir, Muzakir (Universitas Qamarul Huda Badaruddin, 2025)
This study aims to examine the effect of the Two Stay Two Stray (TSTS) learning model on students’ learning outcomes in Social Studies (IPS). The background of this research is the relatively low student achievement, allegedly due to the dominance of conventional teaching methods. The study applied a quasi-experimental method with a pretest-posttest control group design. The participants were seventh-grade students of a public junior high school, divided into an experimental group (using TSTS) and a control group (using conventional methods). Data were collected through a validated achievement test and analyzed using a t-test. The results revealed a significant difference between the experimental and control groups, indicating that the implementation of TSTS had a positive effect on students’ IPS learning outcomes. These findings support constructivist theory, which emphasizes collaboration in learning.